2018
DOI: 10.1097/md.0000000000012784
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of combining capecitabine and temozolomide (CAPTEM) to treat advanced neuroendocrine neoplasms

Abstract: Retrospective studies have suggested that capecitabine combined with temozolomide (CAPTEM) is effective for treating patients with advanced neuroendocrine neoplasms (NENs); however, the efficacy and safety of this regimen needs to be verified by high-quality evidence or results of randomized controlled trials.We carried out a meta-analysis to evaluate the safety and effectiveness of a CAPTEM protocol for patients with advanced NENs. Systematic electronic literature searches were conducted using PubMed, EMBASE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 31 publications
2
33
1
1
Order By: Relevance
“…To our knowledge, this is the first study documenting the efficacy and safety of the CAPTEM regimen in subgroups of patients with high Ki-67 index, divided into G3 NETs and NECs based on the WHO 2017 classification [1]. The median PFS for all patients of 7.1 months (95% CI: 3.27-15.3) was comparable to the range from 3.4 to 6.0 months reported in the recent metanalysis by Lu et al [29]. However, comparison of survival and response based on the Ki-67 level cut-off at 55% showed that results of the treatment were better in G3 NETs than in NECs.…”
Section: Discussionsupporting
confidence: 55%
“…To our knowledge, this is the first study documenting the efficacy and safety of the CAPTEM regimen in subgroups of patients with high Ki-67 index, divided into G3 NETs and NECs based on the WHO 2017 classification [1]. The median PFS for all patients of 7.1 months (95% CI: 3.27-15.3) was comparable to the range from 3.4 to 6.0 months reported in the recent metanalysis by Lu et al [29]. However, comparison of survival and response based on the Ki-67 level cut-off at 55% showed that results of the treatment were better in G3 NETs than in NECs.…”
Section: Discussionsupporting
confidence: 55%
“…148-150 Irinotecan/cisplatin (IP) and etoposide/cisplatin (EP) are the most common chemotherapy regimens for progressive advanced GI NETs. 151 Several studies have shown that capecitabine combined with temozolomide (CAPTEM), 152 bevacizumab, 153 5-fluorouracil, 154 and streptozotocin 155 can be also applied in unresectable GI NETs. Given the current level of evidence of cytotoxic chemotherapy, there remains much controversy about their use.…”
Section: Managementmentioning
confidence: 99%
“…Capecitabine transforms into 5-FU in tumor tissues, and its metabolites can reduce the activity of MGMT, thus enhancing the effect of TMZ on DNA replication. Although the combination of TMZ and capecitabine is recommended for the treatment of pancreatic neuroendocrine neoplasms (29), it remains unknown whether the combination strategy works better than TMZ monotherapy in MPP patients. Prospective clinical trials are warranted.…”
Section: Discussionmentioning
confidence: 99%